Positive electrode active material, positive electrode plate, battery monomer, battery and electric device

CN119404332AActive Publication Date: 2025-02-07CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380048927.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-02-07
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

Existing cathode active materials have deficiencies in balancing the volumetric energy density and rate performance of battery cells. In particular, the cycle performance and lithium ion transmission efficiency of lithium-rich manganese-based materials need to be improved.

Method used

A combination of lithium-rich manganese-based materials and lithium-containing phosphates is used. Through the combination of solid particles and hollow particles, the contact area and compaction density between the electrolyte and the material are increased, thereby improving the transmission efficiency and energy density of lithium ions.

Benefits of technology

It achieves a balance between the rate performance improvement and volumetric energy density of the battery cells, prolongs the cycle life of the battery and increases the energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119404332A_ABST
    Figure CN119404332A_ABST
Patent Text Reader

Abstract

The invention provides a positive active material, a positive pole piece, a battery cell (10), a battery (400) and an electric device, and belongs to the technical field of secondary batteries. The positive electrode active material comprises a lithium-rich manganese-based material and lithium-containing phosphate, the lithium-rich manganese-based material comprises solid particles and hollow particles, and each hollow particle comprises a shell and a cavity formed in the inner side of the shell. And the rate capability and the volume energy density of the battery monomer can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Positive electrode active material, positive electrode sheet, battery cell, battery and electrical device Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a positive electrode active material, a positive electrode plate, a battery cell, a battery, and an electrical device. Background Art

[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] As a component of a battery, the positive electrode active material is crucial to its performance. Therefore, how to provide a positive electrode active material that can balance the volumetric energy density and rate performance of a battery cell is a technical problem that needs to be solved urgently.

[0004] Summary of the Invention

[0005] The present application is made in view of the above technical problems, and aims to provide a positive electrode active material to take into account both the volume energy density and rate performance of a battery cell.

[0006] In order to achieve the above-mentioned objectives, the present application provides a positive electrode active material, a positive electrode plate, a battery cell, a battery and an electrical device.

[0007] In a first aspect, a positive electrode active material is provided, comprising a lithium-rich manganese-based material and a lithium-containing phosphate, wherein the lithium-rich manganese-based material comprises solid particles and hollow particles, and the hollow particles comprise a shell and a cavity arranged inside the shell.

[0008] In the embodiments of the present application, the positive electrode active material includes a lithium-rich manganese-based material and a lithium-containing phosphate. The mutual cooperation of the lithium-rich manganese-based material and the lithium-containing phosphate is beneficial to improving the cycle performance of the battery cell. The lithium-rich manganese-based material includes solid particles and hollow particles. The mutual cooperation of the solid particles and the hollow particles is beneficial to increasing the contact area between the electrolyte and the lithium-rich manganese-based material in the battery cell, which is beneficial to the transmission of lithium ions, thereby improving the rate performance of the battery cell; on the other hand, it is beneficial to increase the compaction density of the positive electrode sheet, thereby increasing the volume energy density of the battery cell. Therefore, the embodiments of the present application can take into account both the volume energy density and rate performance of the battery cell.

[0009] In some embodiments, in the lithium-rich manganese-based material, the ratio of the mass A of the solid particles to the mass B of the hollow particles is 1:1≤A:B≤9:1; optionally, 7:3≤A:B≤8:2; and / or, in the lithium-rich manganese-based material, the ratio of the number E of the solid particles to the number F of the hollow particles is 70:30≤E:F≤96:4; optionally, 85:15≤E:F≤90:10.

[0010] In the above technical solution, the ratio of the mass of the solid particles to the mass of the hollow particles in the lithium-rich manganese-based material satisfies 1:1≤A:B≤9:1, and / or the ratio of the number E of solid particles to the number F of hollow particles is 70:30≤E:F≤96:4. In this way, the lithium-rich manganese-based material has a suitable contact area with the electrolyte, which is conducive to the transmission of lithium ions, thereby helping to improve the rate performance of the battery cell; at the same time, the lithium-rich manganese-based material has a suitable volume, which is conducive to increasing the compaction density of the positive electrode sheet and improving the volume energy density of the battery cell. Optionally, 7:3≤A:B≤8:2, which is conducive to taking into account the rate performance and volume energy density of the battery cell. Optionally, 85:15≤E:F≤90:10, which is conducive to further taking into account the rate performance and volume energy density of the battery cell.

[0011] In some embodiments, the volume average particle size D of the solid particles is V 50 is 2μm to 8μm; optionally, 3μm to 6μm.

[0012] In the above technical solution, the volume average particle size D of the solid particles is V 50 is 2μm to 8μm. In this way, on the one hand, the solid particles have a suitable specific surface area, which is conducive to increasing the contact area between the electrolyte and the solid particles in the lithium-rich manganese-based material, which is conducive to transmitting more lithium ions per unit time and improving the rate performance of the battery cell; on the other hand, the solid particles have a suitable volume, which is conducive to increasing the compaction density of the positive electrode sheet and improving the volume energy density of the battery cell. Optionally, the volume average particle size D of the solid particles is V 50 is 3μm~6μm, which is conducive to further improving the rate performance and volume energy density of battery cells.

[0013] In some embodiments, the volume average particle size D of the hollow particles is V 50 is 5μm to 15μm; optionally, it is 7μm to 12μm.

[0014] In the above technical solution, the volume average particle size D of the hollow particles is V50 is 5μm to 15μm. On the one hand, the hollow particles have a suitable specific surface area, which is beneficial to increase the contact area between the electrolyte and the hollow particles of the lithium-rich manganese-based material, thereby facilitating the transmission of more lithium ions per unit time and improving the rate performance of the battery cell. On the other hand, the volume occupied by the hollow particles is relatively suitable, which is beneficial to improving the volume energy density of the battery cell. Optionally, the volume average particle size D of the hollow particles is V 50 is 7μm~12μm, which is conducive to taking into account the rate performance and volume energy density of the battery cell.

[0015] In some embodiments, the volume average particle size D of the hollow particles is V 50 is greater than the volume average particle size D of the solid particles V 50; Optionally, the volume average particle size D of the hollow particles V 50 and the volume average particle size D of the solid particles v 50 is 3μm~10μm; further optionally, the difference is 4μm~8μm; and / or the number average particle size of the hollow particles is larger than the number average particle size of the solid particles; optionally, the difference between the number average particle size of the hollow particles and the number average particle size of the solid particles is 3μm~10μm; further optionally, the difference is 4μm~8μm.

[0016] In the above technical solution, the volume average particle size D of the hollow particles is V 50 is larger than the volume average particle size D of solid particles V 50; and / or, the number average particle size of the hollow particles is larger than the number average particle size of the solid particles, so that the solid particles can fill the gaps between the hollow particles, which is beneficial to improving the compaction density of the positive electrode sheet, thereby helping to improve the energy density of the battery cell. Optionally, the volume average particle size D of the hollow particles is V 50 and the volume average particle size D of solid particles V 50 is 3μm~10μm or further optionally 4μm~8μm; and / or, the difference between the number average particle size of the hollow particles and the number average particle size of the solid particles is 3μm~10μm or further optionally 4μm~8μm, which is conducive to achieving a reasonable combination of solid particles and hollow particles, and better filling the gaps between hollow particles, thereby increasing the compaction density of the positive electrode sheet and improving the energy density of the battery cell.

[0017] In some embodiments, the size of the cavity of the hollow particle is 2 μm to 10 μm; alternatively, 4 μm to 7 μm.

[0018] In the above technical solution, the hollow particle cavity size is 2μm to 10μm. On the one hand, the hollow particle has a suitable specific surface area, which facilitates the transmission of more lithium ions per unit time, thereby improving the rate performance of the battery cell. On the other hand, the hollow particle occupies an appropriate volume, which helps to improve the volumetric energy density of the battery cell. Optionally, the hollow particle cavity size is 4μm to 7μm, which helps to balance the rate performance and volumetric energy density of the battery cell.

[0019] In some embodiments, the volume average particle size D of the lithium-containing phosphate V 50 is 0.3μm to 1.5μm; optionally, it is 0.6μm to 1.2μm.

[0020] In the above technical solution, by setting the volume average particle size of the lithium-containing phosphate in the positive electrode active material to no more than 1.5 μm, it is beneficial to reduce the volume of the lithium-containing phosphate and improve the volume energy density of the battery cell; the volume average particle size of the lithium-containing phosphate is no less than 0.3 μm, which is beneficial to maintain a relatively appropriate contact area between the lithium-containing phosphate and the electrolyte, thereby improving the rate performance of the battery cell. V 50 is 0.6μm~1.2μm, which is conducive to further taking into account the rate performance and volume energy density of the battery cell.

[0021] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the lithium-rich manganese-based material is P, 10 wt%≤P<100 wt%, optionally, 30 wt%≤P≤70 wt%.

[0022] In the above technical solution, by reasonably setting the mass proportion of lithium-rich manganese-based materials in the positive electrode active material, it is beneficial to take into account both the volume energy density and rate performance of the battery cell.

[0023] In some embodiments, the gram capacity Q of the lithium-rich manganese-based material is ≥153 mAh / g; optionally, Q ≥158 mAh / g.

[0024] In the above technical solution, the gram capacity Q of the lithium-rich manganese-based material is ≥153 mAh / g, which is conducive to improving the energy density of the battery cell. Optionally, Q is ≥158 mAh / g, which is conducive to further improving the energy density of the battery cell.

[0025] In some embodiments, the general formula of the lithium-rich manganese-based material is nLi2MnO3·(1-n)Li 1+x1 Ni x2 Mn x3 M 1 x4O2, where 0.1≤n≤0.3, 0≤x1≤0.1, 0.3≤x2<1, 0<x3≤0.7, 0≤x4≤0.1, M 1 The lithium-rich manganese-based material includes one or more of Na, Mg, Al, Ca, Ba, V, Zn, Ti, Fe, Co, Cr, Nb, W, Mo, Zr, Ta, and Hf. In this way, it is convenient to flexibly select the lithium-rich manganese-based material according to actual needs.

[0026] In some embodiments, the lithium-containing phosphate has the general formula Li 1+y1 Fe y2 Mn y3 M 2 y4 PO4, where 0≤y1≤0.1, 0≤y2≤1, 0≤y3≤1, 0≤y4≤0.1, M 2 The lithium phosphate may include transition metal elements other than Fe and Mn and one or more non-transition metal elements.

[0027] In a second aspect, a positive electrode plate is provided, comprising the positive electrode active material in the first aspect and any possible implementation thereof.

[0028] In one possible implementation, the compaction density of the positive electrode sheet is 2.70 g / cm 3 ~2.90g / cm 3 , optionally, 2.75 g / cm 3 ~2.85g / cm 3 In this way, the battery cell has a higher volume energy density.

[0029] In a third aspect, a battery cell is provided, wherein the battery cell includes the positive electrode sheet in the second aspect and any possible implementation thereof.

[0030] In a fourth aspect, a battery is provided, comprising the battery cell according to the third aspect.

[0031] In a fifth aspect, an electrical device is provided, wherein the electrical device includes the battery in the fourth aspect.

[0032] In the embodiments of the present application, the positive electrode active material includes a lithium-rich manganese-based material and a lithium-containing phosphate. The mutual cooperation of the lithium-rich manganese-based material and the lithium-containing phosphate is beneficial to improving the cycle performance of the battery cell. The lithium-rich manganese-based material includes solid particles and hollow particles. The mutual cooperation of the solid particles and the hollow particles is beneficial to increasing the contact area between the electrolyte and the lithium-rich manganese-based material in the battery cell, which is beneficial to the transmission of lithium ions, thereby improving the rate performance of the battery cell; on the other hand, it is beneficial to increase the compaction density of the positive electrode sheet, thereby increasing the volume energy density of the battery cell. Therefore, the embodiments of the present application can take into account both the volume energy density and rate performance of the battery cell. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] To more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some embodiments of the present application. Those skilled in the art can also derive other drawings based on the drawings without inventive effort. In the drawings, the drawings are not drawn to scale.

[0034] FIG1 is a schematic diagram of a battery cell according to an embodiment of the present application.

[0035] FIG2 is a schematic diagram of the explosion structure of a battery cell according to an embodiment of the present application.

[0036] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.

[0037] FIG4 is a schematic diagram of a battery according to an embodiment of the present application.

[0038] FIG5 is a schematic diagram of an exploded structure of a battery according to an embodiment of the present application.

[0039] FIG6 is a schematic diagram of an electrical device according to an embodiment of the present application. DETAILED DESCRIPTION

[0040] Below, the embodiments of the positive electrode active material, positive electrode sheet, battery cell, battery and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0041] In the description of this application, it should be noted that, unless otherwise specified, "plurality" means more than two; terms such as "upper," "lower," "left," "right," "inner," and "outer" indicating directions or positional relationships are merely for the purpose of facilitating the description of this application and simplifying the description, and do not indicate or imply that the devices or components referred to must have a specific orientation, be constructed, or operate in a specific orientation. Therefore, they should not be construed as limiting this application. Furthermore, terms such as "first," "second," and "third" are used for descriptive purposes only and should not be construed as indicating or implying relative importance.

[0042] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0043] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0044] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0045] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0046] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0047] In recent years, power batteries have been widely used in power tools, electronic products, electric vehicles, aerospace and other fields due to their high energy density and long service life, and have thus achieved great development. Generally, a power battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. Among them, the electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which prevents the positive and negative electrodes from short-circuiting while allowing ions to pass through, so that the electrochemical reaction of the power battery proceeds normally.

[0048] This application uses lithium-ion batteries as an example. Lithium-ion batteries are a typical type of power battery. Because they rely on the chemical reaction of lithium ions intercalating and deintercalating between the positive and negative electrodes to charge and discharge, lithium-ion batteries are also called rocking-chair batteries. During the charging process of a lithium-ion battery, lithium ions are released from the positive electrode, transferred through the electrolyte, and embedded in the active material of the negative electrode. During the discharge process, lithium ions are released from the negative electrode, transferred through the electrolyte, and embedded in the active material of the positive electrode.

[0049] It should be understood that the "lithium insertion" and "intercalation" processes described in this application refer to the process in which lithium ions are embedded in the positive electrode active material or the negative electrode active material due to an electrochemical reaction, and the "de-lithiumization", "de-intercalation" and "de-intercalation" processes described in this application refer to the process in which lithium ions are removed from the positive electrode active material or the negative electrode active material due to an electrochemical reaction.

[0050] Lithium-ion battery cathode active materials typically use lithium-containing transition metal oxides or compounds, such as lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, ternary materials, and lithium-rich manganese-based materials. Among these, lithium-rich manganese-based materials are primarily based on the relatively inexpensive element manganese, offering low material cost and high specific capacity, which contributes to improving the energy density of lithium-ion batteries. However, as the charge and discharge processes progress, the structure of lithium-rich manganese-based materials changes, resulting in poor battery cycling performance.

[0051] In some treatment methods, a lithium-containing phosphate (such as lithium iron phosphate) is mixed with a lithium-rich manganese-based material to prepare the positive electrode active material to improve the battery's cycling performance. However, the batteries obtained by this treatment method have poor rate performance.

[0052] In view of this, embodiments of the present application provide a positive electrode active material comprising a lithium-rich manganese-based material and a lithium-containing phosphate, wherein the lithium-rich manganese-based material comprises solid particles and hollow particles. The combination of solid particles and hollow particles increases the contact area between the lithium-rich manganese-based material and the electrolyte, thereby facilitating the transmission of lithium ions and, in turn, improving the rate performance of the battery cell.

[0053] [Positive electrode active material]

[0054] An embodiment of the present application provides a positive electrode active material, including a lithium-rich manganese-based material and a lithium-containing phosphate.

[0055] Lithium-rich manganese-based materials include solid particles and hollow particles. Lithium-rich manganese-based materials include two types of particles, namely solid particles and hollow particles.

[0056] Hollow particles include a shell and a cavity disposed inside the shell. In other words, hollow particles can be understood as particles with a cavity disposed inside the particle.

[0057] Solid particles can be understood as particles without a cavity inside. When the particle size of solid particles is the same as that of hollow particles, the specific surface area of ​​hollow particles is larger; when solid particles and hollow particles have the same mass, the surface area of ​​hollow particles is larger.

[0058] The gram capacity of lithium-rich manganese-based materials is relatively high, and the structure of lithium-containing phosphates is relatively stable. The positive electrode active materials including lithium-rich manganese-based materials and lithium-containing phosphates have suitable gram capacity and stability. When the positive electrode active materials are used to prepare battery cells, the obtained battery cells can have higher energy density and better cycle performance.

[0059] Compared to lithium-rich manganese-based materials that are all solid particles, the lithium-rich manganese-based materials of the present application embodiment include solid particles and hollow particles, thus having a larger specific surface area. This increases the contact area between the lithium-rich manganese-based materials and the electrolyte in the battery cell, facilitating the transfer of lithium ions and thus improving the rate performance of the battery cell.

[0060] The rate performance of a battery cell is related to the transmission of lithium ions. Generally speaking, the more lithium ions transmitted per unit time, the more beneficial it is to improving the rate performance of the battery cell.

[0061] In addition, compared to lithium-rich manganese-based materials which are all hollow particles, the lithium-rich manganese-based materials of the embodiments of the present application include solid particles and hollow particles, which is beneficial to reducing the space occupied by the positive electrode active material, thereby facilitating the improvement of the volume energy density of the battery cell.

[0062] The shapes of the solid particles and hollow particles in the embodiments of the present application may include: spherical, approximately spherical (such as ellipsoidal), irregular, and other shapes.

[0063] In the embodiment of the present application, the positive electrode active material includes a lithium-rich manganese-based material and a lithium-containing phosphate, which is beneficial to improving the cycle performance of the battery cell; the lithium-rich manganese-based material includes solid particles and hollow particles. Through the combination of solid particles and hollow particles, it is beneficial to improve the rate performance of the battery cell with a higher energy density, thereby helping to take into account the volume energy density and rate performance of the battery cell.

[0064] In some embodiments, in the lithium-rich manganese-based material, the ratio of the mass A of the solid particles to the mass B of the hollow particles is 1:1≤A:B≤9:1, for example, A:B is 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1 and any range consisting of the above values; and / or, in the lithium-rich manganese-based material, the ratio of the number E of the hollow particles to the number F of the solid particles is 70:30≤E:F≤96:4, for example, E:F is 7:3, 5:1, 10:1, 13:1, 24:1 and any range consisting of the above values.

[0065] The mass A of the solid particles and the mass B of the hollow particles can be obtained by weighing. For example, in the process of preparing the positive electrode active material, the lithium-rich manganese-based material and the lithium-containing phosphate are mixed to obtain the positive electrode active material. The lithium-rich manganese-based material is obtained by mixing the lithium-rich manganese-based material of the solid particles with the lithium-rich manganese-based material of the hollow particles. In the preparation process of the lithium-rich manganese-based material, a certain mass of hollow particles and a certain mass of solid particles can be weighed separately (for example, using a balance) to obtain the mass of the hollow particles and the mass of the solid particles, and then the hollow particles and the solid particles are mixed.

[0066] Alternatively, the cross-sections of the solid and hollow particles can be obtained by cutting the positive electrode sheet, and the volume ratio of the solid and hollow particles can be calculated based on the diameter of the cross-sections, and then the mass ratio of the solid and hollow particles can be calculated based on the volume ratio and the average density of the solid and hollow particles.

[0067] The ratio E:F of the number E of solid particles to the number F of hollow particles can be calculated based on the ratio A:B between the mass A of the solid particles and the mass B of the hollow particles, as well as the particle size or volume and average density of the solid and hollow particles. Alternatively, the positive electrode sheet can be cut to obtain a cross-section of the positive electrode sheet, and the cross-section can be observed using a scanning electron microscope or other means to obtain the ratio of the number of solid particles to that of hollow particles.

[0068] When A:B is not less than 1:1, the battery cell can have a higher volume energy density; when A:B is not greater than 9:1, there is a suitable contact area between the lithium-rich manganese-based material and the electrolyte, which is conducive to the transmission of lithium ions, thereby helping to improve the rate performance of the battery cell.

[0069] Optionally, 7:3≤A:B≤8:2, for example, A:B is 7:3, 3:1, 8:2, or any range thereof. This helps to further balance the rate performance and volume energy density of the battery cell.

[0070] Optionally, 85:15≤E:F≤90:10, for example, E:F is 85:15, 7:1, 9:1, or any range thereof. This helps to further balance the rate performance and volume energy density of the battery cell.

[0071] In some embodiments, the volume average particle size D of the solid particles is V 50 is 2 μm to 8 μm; alternatively, 3 μm to 6 μm. For example, the volume average particle size D of the solid particles is V 50 is 2 μm, 3 μm, 4 μm, 5.5 μm, 6 μm, 8 μm or any other value within the above range.

[0072] D V 50 may refer to the particle size corresponding to the particles whose cumulative volume particle size distribution percentage reaches 50%.

[0073] Volume average particle size D of solid particles V 50 and the volume average particle size D of the hollow particles V 50 can be obtained by laser particle size analysis. For example, the powder particles are first dispersed in an appropriate amount of solvent to form a dispersion; the dispersion is then placed in a laser particle size analyzer to measure the particle size. Alternatively, the powder particles can be lithium-rich manganese-based material powder obtained during the preparation process, or powder obtained from the electrode (for example, powder of positive electrode active material obtained from the positive electrode electrode by a specific method, after removing the binder and other substances).

[0074] The volume average particle size D of solid particles VWhen the volume average particle size D of the solid particles is not less than 2 μm, the solid particles have a suitable specific surface area, which is beneficial to increase the contact area between the electrolyte and the solid particles, and is beneficial to transmit more lithium ions per unit time, which is beneficial to improve the rate performance of the battery cell; when the volume average particle size D of the solid particles is not less than 2 μm, the solid particles have a suitable specific surface area, which is beneficial to increase the contact area between the electrolyte and the solid particles, and is beneficial to transmit more lithium ions per unit time, which is beneficial to improve the rate performance of the battery cell; V When the particle size is not greater than 8 μm, the solid particles have a suitable volume, which is beneficial to improving the compaction density of the positive electrode sheet and the volume energy density of the battery cell.

[0075] Optionally, the volume average particle size D of the solid particles V 50 is 3μm~6μm, which is conducive to improving both the rate performance and volume energy density of the battery cell.

[0076] In some embodiments, the volume average particle size D of the hollow particles is V 50 is 5 μm to 15 μm. For example, the volume average particle size D of the hollow particles is V 50 is 5 μm, 6 μm, 7 μm, 8 μm, 10 μm, 12 μm, 13 μm, 15 μm or any other value within the above range.

[0077] The volume average particle size D of the hollow particles V When the volume average particle size D of the hollow particles is not less than 5 μm, the hollow particles have a suitable specific surface area, which is beneficial to increase the contact area between the electrolyte and the hollow particles, and is beneficial to transmit more lithium ions per unit time, which is beneficial to improve the rate performance of the battery cell; when the volume average particle size D of the hollow particles is not less than 5 μm, the hollow particles have a suitable specific surface area, which is beneficial to increase the contact area between the electrolyte and the hollow particles, and is beneficial to transmit more lithium ions per unit time, which is beneficial to improve the rate performance of the battery cell; V When the particle size is not greater than 15 μm, it is beneficial to reduce the volume occupied by the hollow particles, thereby improving the energy density of the battery cell.

[0078] Optionally, the volume average particle size D of the hollow particles V 50 is 7μm~12μm, which is conducive to taking into account the rate performance and volume energy density of the battery cell.

[0079] In some embodiments, the volume average particle size D of the hollow particles is V 50 is larger than the volume average particle size D of solid particles V 50; and / or, the number average particle size of the hollow particles is greater than the number average particle size of the solid particles.

[0080] The number average particle size may refer to the particle size corresponding to particles where the cumulative number of particles in the particle size distribution percentage reaches 50%.

[0081] Alternatively, the number average particle size can be measured using the same testing method as the volume average particle size, for example, by using a laser particle size analyzer.

[0082] Alternatively, the number average particle size can be measured indirectly or directly by the following methods: cutting the positive electrode sheet to obtain a cross-section of the positive electrode sheet, and observing the cross-section using a scanning electron microscope. The number and size (particle size) of the hollow particles and solid particles in a specific area or the entire area are measured to determine the average size (particle size) of the hollow particles and solid particles.

[0083] In this embodiment, compared with hollow particles, solid particles have a smaller volume, and solid particles can fill the gaps between hollow particles, thereby helping to improve the compaction density of the positive electrode sheet and the energy density of the battery cell.

[0084] Optionally, the volume average particle size D of the hollow particles V 50 and the volume average particle size D of solid particles V 50 is 3 μm to 10 μm; and / or the difference between the number average particle size of the hollow particles and the number average particle size of the solid particles is 3 μm to 10 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any other value within the above range. In this way, the solid particles can better fill the gaps between the hollow particles, which is conducive to further improving the compaction density of the positive electrode sheet and the energy density of the battery cell.

[0085] Optionally, the volume average particle size D of the hollow particles V 50 and the volume average particle size D of solid particles V 50 is 4 μm to 8 μm; and / or the difference between the number average particle size of the hollow particles and the number average particle size of the solid particles is 4 μm to 8 μm. This helps the solid particles better fill the gaps between the hollow particles, achieving a reasonable combination between the larger hollow particles and the smaller solid particles, thereby improving the compaction density of the positive electrode sheet and the energy density of the battery cell.

[0086] In some embodiments, the size of the cavity of the hollow particle is 2 μm to 10 μm. For example, the size of the cavity of the hollow particle is 2 μm, 3 μm, 4 μm, 6 μm, 7 μm, 9 μm, 10 μm or any other value within the above range.

[0087] Hollow particles can include particles of various shapes. For example, hollow particles are spherical particles or ellipsoidal particles.

[0088] For spherical hollow particles, the size of the cavity of the hollow particle can be understood as the inner diameter of the hollow particle. The hollow particle has a shell and a cavity inside the shell. The diameter of the shell is the outer diameter of the hollow particle, and the size of the cavity inside the shell is the inner diameter of the hollow particle.

[0089] For ellipsoidal hollow particles, the size of the cavity of the hollow particle can be understood as the average of the maximum and minimum dimensions of the cavity of the hollow particle. For example, if the cross-section of the ellipsoidal hollow particle is an ellipse, the size of the cavity is the average of the major and minor axes of the ellipse.

[0090] For other irregular hollow particles, the size of the cavity can be understood as the average of the maximum size and the minimum size of the cavity.

[0091] The following describes the measurement of the cavity size of spherical hollow particles as an example. The cavity size of a hollow particle can be measured using the following method: The hollow particle is cut using an argon ion beam polisher to obtain a particle cross-section; multiple images of the particle cross-section at the same magnification are obtained using a scanning electron microscope; the inner diameters of the particle cross-sections in the images are counted and the average of the multiple inner diameters is calculated, which is used as the cavity diameter of the hollow particle.

[0092] When the size of the cavity of the hollow particles is not less than 2 μm, the hollow particles have a suitable specific surface area, which is beneficial to increase the contact area between the electrolyte and the hollow particles, which is beneficial to the transmission of more lithium ions per unit time, and is beneficial to improving the rate performance of the battery cell; when the size of the cavity of the hollow particles is not greater than 10 μm, the hollow particles have a suitable volume, which is beneficial to increase the compaction density of the positive electrode sheet, thereby facilitating the improvement of the volume energy density of the battery cell.

[0093] Optionally, the size of the cavity of the hollow particles is 4 μm to 7 μm, which is beneficial for taking into account both the rate performance and volume energy density of the battery cell.

[0094] In some embodiments, the volume average particle size D of the lithium-containing phosphate is V 50 is 0.3 μm to 1.5 μm, for example, 0.3 μm, 0.6 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm or any other value within the above range.

[0095] The volume average particle size D of lithium-containing phosphate V When the volume average particle size of the lithium-containing phosphate is not less than 0.3 μm, it is beneficial to maintain a relatively suitable contact area between the lithium-containing phosphate and the electrolyte, thereby improving the rate performance of the battery cell.

[0096] Optionally, the volume average particle size D of the lithium-containing phosphate V50 is 0.6μm~1.2μm. This is conducive to further improving the rate performance and volume energy density of the battery cell.

[0097] In some embodiments, based on the total mass of the positive electrode active material, the mass proportion of the lithium-rich manganese-based material is P, 10wt%≤P<100wt%, for example, P is 10wt%, 20wt%, 30wt%, 50wt%, 70wt%, 80wt%, 90wt%, 95wt% or any other value within the above range.

[0098] The mass proportion of the lithium-rich manganese-based material is the ratio of the mass of the lithium-rich manganese-based material to the mass of the positive electrode active material.

[0099] Alternatively, the mass fraction of the lithium-rich manganese-based material can be calculated based on the particle size and average density of the solid particles and hollow particles in the lithium-rich manganese-based material, and the particle size and average density of the lithium-containing phosphate. Alternatively, it can be obtained by other testing methods, which are not limited in the present embodiment.

[0100] When P is not less than 10wt%, the positive electrode material contains a suitable content of lithium-rich manganese-based materials, which is beneficial to improving the energy density of the battery cell; when P is less than 100wt%, the positive electrode material contains some lithium-containing phosphates, which is beneficial to improving the cycle performance of the battery cell.

[0101] Optionally, 30 wt% ≤ P ≤ 70 wt%, which is beneficial for further taking into account both the energy density and cycle performance of the battery cell.

[0102] Optionally, the positive electrode active material may also include other materials, such as lithium cobalt oxide, etc., which is not limited in the embodiment of the present application.

[0103] In some embodiments, the gram capacity Q of the lithium-rich manganese-based material is ≥153 mAh / g, such as 153 mAh / g, 158 mAh / g, 163 mAh / g, or a greater value, which is beneficial to improving the energy density of the battery cell.

[0104] Gram capacity refers to the ratio of the amount of electricity that an active material can release to the mass of the active material.

[0105] The gram capacity of lithium-rich manganese-based materials can be measured by the following method. The lithium-rich manganese-based material is used as the positive electrode active material, and a lithium-ion battery is prepared using the positive electrode active material, and then the lithium-ion battery is subjected to charge and discharge tests; the ratio of the discharge capacity of the lithium-ion battery obtained according to the charge and discharge test to the mass of the lithium-rich manganese-based material is the gram capacity of the lithium-rich manganese-based material. Among them, the charge and discharge test method is as follows: under a constant temperature environment of 25°C, the lithium-ion battery is discharged to 2.5V at 1 / 3C; let it stand for 5 minutes, charge it to 4.35V at 1 / 3C, and then charge it at a constant voltage at 4.35V to a current ≤0.05C; let it stand for 5 minutes, and then discharge it to 2.5V at 1 / 3C. The amount of electricity released by the lithium-ion battery during this discharge process is the discharge capacity.

[0106] Optionally, the gram capacity Q of the lithium-rich manganese-based material is ≥158 mAh / g, which is conducive to further improving the energy density of the battery cell.

[0107] In the embodiments of the present application, different gram capacities can be achieved by selecting different specific types of lithium-rich manganese-based materials.

[0108] In some embodiments, the general formula of the lithium-rich manganese-based material is nLi2MnO3·(1-n)Li 1+x1 Ni x2 Mn x3 M 1 x4 O2, where 0.1≤n≤0.3, 0≤x1≤0.1, 0.3≤x2<1, 0<x3≤0.7, 0≤x4≤0.1, M 1 The lithium-rich manganese-based material includes one or more of Na, Mg, Al, Ca, Ba, V, Zn, Ti, Fe, Co, Cr, Nb, W, Mo, Zr, Ta, and Hf. In this way, it is convenient to flexibly select the lithium-rich manganese-based material according to actual conditions.

[0109] In some embodiments, the lithium-rich manganese-based material can be 0.1Li2MnO3·0.9LiNi 0.5 Mn 0.5 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.5 O2、0.25Li2MnO3·0.75LiNi 0.5 Mn 0.5 O2 and 0.15Li2MnO3·0.85LiNi 0.5 Mn 0.5 O2、0.3Li2MnO3·0.7LiNi 0.5 Mn 0.5 At least one of O2.

[0110] In some embodiments, the lithium-rich manganese-based material can be 0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Mg 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Al 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 V 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Ti 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Co 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Nb 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 W 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Mo 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Zr 0.05 O2、0.2Li2MnO3·0.8LiNi 0.5 Mn 0.45 Ta 0.05 At least one of O2.

[0111] In some embodiments, M 1 Na, sodium ions can replace some lithium ions.

[0112] It should be noted that the general formula of the lithium-rich manganese-based material given in the embodiment of the present application may be a general formula under a rational state. The ideal state may include that when preparing the positive electrode active material, the lithium-rich manganese-based material added satisfies the above general formula. After the positive electrode active material is prepared into a battery cell, due to various situations such as the deintercalation or consumption of lithium ions, the actual content of lithium ions may be reduced compared to the general formula of the lithium-rich manganese-based material. Similarly, the actual content of oxygen ions may also be reduced.

[0113] In some embodiments, the lithium-containing phosphate has the general formula Li 1+y1 Fe y2 Mny3 M 2 y4 PO4, where 0≤y1≤0.1, 0≤y2≤1, 0≤y3≤1, 0≤y4≤0.1, M 2 The lithium phosphate may include transition metal elements other than Fe and Mn and one or more non-transition metal elements.

[0114] In some embodiments, the lithium-containing phosphate may be LiFePO4, Li 1.1 FePO4, LiMnPO4, LiMn 0.5 Fe 0.5 PO4、LiFe 0.5 Mn 0.45 Mg 0.05 PO4、LiFe 0.5 Mn 0.45 Al 0.05 PO4、LiFe 0.5 Mn 0.45 V 0.05 PO4、LiFe 0.5 Mn 0.45 Ti 0.05 PO4、LiFe 0.5 Mn 0.45 Co 0.05 PO4、LiFe 0.5 Mn 0.45 Nb 0.05 PO4、 LiFe 0.5 Mn 0.45 W 0.05 PO4、LiFe 0.5 Mn 0.45 Mo 0.05 PO4、LiFe 0.5 Mn 0.45 Zr 0.05 PO4、LiFe 0.5 Mn 0.45 Ta 0.05 At least one of PO4.

[0115] Similarly, referring to the description above, the general formula of the lithium phosphate actually measured may be Li 1+a Fe 1-x2- y2 Mn x2 M2 y2 PO 4+b , a<0, b<0.

[0116] In some embodiments, lithium-containing phosphates can be modified by surface coating. For example, LiFePO4 can be coated with carbon or polymer to enhance its conductivity. Alternatively, the material can be modified by doping with metal cations or other ions. For example, LiFePO4 can be doped with high-valent metal cations to enhance its conductivity.

[0117] [Positive electrode]

[0118] An embodiment of the present application provides a positive electrode plate, comprising the positive electrode active material in any possible embodiment described above.

[0119] The positive electrode sheet may include a positive electrode current collector and a positive electrode material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode active material.

[0120] As an example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode material layer is disposed on either or both of the two opposite surfaces of the positive electrode current collector.

[0121] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0122] In some embodiments, the compaction density of the positive electrode sheet at a pressure of 400 kN is 2.7 g / cm 3 ~2.9g / cm 3 ; Optionally, 2.75g / cm 3 ~2.85g / cm 3 For example, the compaction density of the positive electrode sheet under a pressure of 400KN is 2.7g / cm 3 , 2.75g / cm 3 , 2.8g / cm 3 , 2.85g / cm 3 , 2.9g / cm 3 This is beneficial to improving the energy density of battery cells.

[0123] After the positive electrode sheet is cold pressed at different pressures, the compaction density may be different. Optionally, the cold pressing pressure of the positive electrode sheet does not exceed 800 kN.

[0124] In some embodiments, the positive electrode material layer includes a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylate resin.

[0125] In some embodiments, the positive electrode material layer includes a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0126] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder, the additives and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0127] [Negative electrode]

[0128] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode active material.

[0129] As an example, the negative electrode current collector has two surfaces facing each other in its thickness direction, and the negative electrode material layer is disposed on either or both of the two facing surfaces of the negative electrode current collector.

[0130] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0131] In some embodiments, the negative electrode active material may be a negative electrode active material for a battery that is well known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxides, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxides, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.

[0132] In some embodiments, the negative electrode material layer may further include a binder. The binder may include at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0133] In some embodiments, the negative electrode material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0134] In some embodiments, the negative electrode material may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0135] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0136] [Electrolytes]

[0137] The electrolyte conducts ions between the positive and negative electrodes. The present invention does not specifically limit the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.

[0138] In some embodiments, the electrolyte is an electrolyte solution comprising an electrolyte salt and a solvent.

[0139] In some embodiments, the electrolyte salt may include at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.

[0140] In some embodiments, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methylpropyl carbonate, ethylpropyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane, dimethyl sulfone, methyl ethyl sulfone, and diethyl sulfone.

[0141] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.

[0142] [Isolator]

[0143] In some embodiments, the battery cell further includes a separator. The present invention has no particular limitation on the type of separator, and any known porous separator with good chemical and mechanical stability can be selected.

[0144] In some embodiments, the separator may be made of at least one of fiberglass, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a separator membrane, which may be a single-layer film or a multi-layer composite film, without particular limitation. When the separator membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.

[0145] In some embodiments, the positive electrode sheet, the negative electrode sheet, and the separator can be formed into an electrode assembly through a winding process or a lamination process.

[0146] [Battery Cell]

[0147] An embodiment of the present application provides a battery cell, comprising the positive electrode sheet in any of the above embodiments.

[0148] The embodiment of the present application has no particular limitation on the shape of the battery cell, which can be cylindrical, square, or any other shape. For example, FIG1 shows a battery cell 10 with a square structure as an example.

[0149] Figure 2 is a schematic diagram of the explosion structure of a battery cell according to an embodiment of the present application. In some embodiments, the battery cell may include an outer packaging. The outer packaging can be used to encapsulate the electrode assembly and the electrolyte. Referring to Figure 2, the outer packaging may include a shell 21 and a cover plate 22. The shell 21 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 21 has an opening connected to the receiving cavity, and the cover plate 22 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can be formed into an electrode assembly 23 through a winding process or a lamination process. The electrode assembly 23 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 23. The number of electrode assemblies 23 in the battery cell 10 can be one or more, which can be selected according to specific actual needs.

[0150] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell. Alternatively, the outer packaging of the battery cell may be a soft shell, such as a pouch-type soft shell. The soft shell may be made of plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0151] In some embodiments, the battery cells 10 may be assembled into a battery module. The battery module may contain one or more battery cells 10 , and the specific number may be selected according to the application and capacity of the battery module.

[0152] Figure 3 is a schematic diagram of a battery module 300 according to an embodiment of the present application. Referring to Figure 3 , in the battery module 300, a plurality of battery cells 10 may be arranged sequentially along the length of the battery module 300. Of course, they may also be arranged in any other manner.

[0153] In some embodiments, the battery modules 300 may also be assembled into a battery. The battery may contain one or more battery modules 300 , and the specific number may be selected according to the application and capacity of the battery.

[0154] [Battery]

[0155] An embodiment of the present application provides a battery, comprising the battery cell described in the above embodiment.

[0156] Figure 4 is a schematic diagram of a battery according to an embodiment of the present application, and Figure 5 is a schematic diagram of a battery according to an embodiment of the present application. As an example, referring to Figures 4 and 5 , a battery 400 may include a battery box and multiple battery modules 300 disposed within the battery box. The battery box includes an upper box body 401 and a lower box body 402. The upper box body 401 can be placed over the lower box body 402 to form an enclosed space for accommodating the battery modules 300. The multiple battery modules 300 can be arranged in any manner within the battery box.

[0157] The battery cells 10 can directly form a battery 400. In other words, the battery cells 10 do not need to be formed into a battery module first, but can directly form a battery 400. In the embodiment of the present application, there is no limitation on the number of battery cells included in the battery.

[0158] [Electrical devices]

[0159] An embodiment of the present application provides an electrical device, comprising the battery described in the above embodiment.

[0160] Figure 6 is a schematic diagram of an electric device according to an embodiment of the present application. As an example, the electric device is a vehicle.

[0161] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.

[0162] Example

[0163] Example 1

[0164] In Example 1, the positive electrode active material includes a lithium-rich manganese-based material and a lithium-containing phosphate. The lithium-containing phosphate is lithium iron phosphate LiFePO4, and the lithium-rich manganese-based material is 0.2Li2MnO3·0.8LiNi 0.5 Mn 0.5 O2.

[0165] Lithium iron phosphate D V 50 is 0.5 μm, the gram capacity of the lithium-rich manganese-based material is 158 mAh / g, and based on the total mass of the positive electrode active material, the mass content of the lithium-rich manganese-based material in the positive electrode active material is 50 wt%.

[0166] The mass ratio of solid particles to hollow particles in the lithium-rich manganese-based material is A:B, which is 8:2. V 50 is 5 μm, D of hollow particles V 50 is 9 μm, and the size of the cavity of the hollow particles is 4 μm.

[0167] Examples 2-4

[0168] The difference between Example 2-4 and Example 1 is that A:B is different.

[0169] In Examples 2-4, the ratios of A:B are 7:3, 9:1, and 5:5, respectively.

[0170] Examples 5-8

[0171] The difference between Examples 5-8 and Example 1 is that the volume average particle size D of the solid particles is V 50 different.

[0172] In Examples 5-8, the volume average particle size D of the solid particles is V 50 are: 2μm, 3μm, 6μm, 8μm.

[0173] Examples 9-12

[0174] The difference between Examples 9-12 and Example 1 is that the volume average particle size D of the hollow particles is V 50 different.

[0175] In Examples 9-12, the volume average particle size D of the hollow particles is V 50 are: 6μm, 7μm, 12μm, 15μm respectively.

[0176] Examples 13-15

[0177] The difference between Examples 13-14 and Example 1 is that the sizes of the cavities of the hollow particles are different.

[0178] In Examples 13-14, the sizes of the cavities of the hollow particles are 2 μm and 7 μm, respectively.

[0179] The difference between Example 15 and Example 1 is that the volume average particle size D of the hollow particles is V 50. The size of the cavity of the hollow particles and the volume average particle size D of the hollow particles V 50 and the volume average particle size D of solid particles V The difference of 50 is different.

[0180] In Example 15, the volume average particle size D of the hollow particles is V 50 is 15 μm, the size of the cavity of the hollow particles is 10 μm, and the volume average particle size D of the hollow particles is V 50 and the volume average particle size D of solid particles V The difference of 50 is 10μm.

[0181] Examples 16-17

[0182] The difference between Examples 16-17 and Example 1 is that the gram capacity of the lithium-rich manganese-based material is different.

[0183] In Examples 16 and 17, the gram capacities of the lithium-rich manganese-based materials are 153 mAh / g and 163 mAh / g, respectively.

[0184] Correspondingly, in Examples 16 and 17, the lithium-rich manganese-based materials are 0.25Li2MnO3·0.75LiNi0.5 Mn 0.5 O2 and 0.15Li2MnO3·0.85LiNi 0.5 Mn 0.5 O2.

[0185] Examples 18-21

[0186] The difference between Examples 18-21 and Example 1 is that the volume average particle size D of lithium iron phosphate is V 50 different.

[0187] In Examples 18-21, the volume average particle size D of lithium iron phosphate V 50 are: 0.5μm, 0.6μm, 1.2μm, 1.5μm respectively.

[0188] Examples 22-23

[0189] The difference between Examples 22-23 and Example 1 is that the mass ratio of the lithium-rich manganese-based material to the positive electrode active material is different.

[0190] In Examples 22-23, the mass ratios of the lithium-rich manganese-based material to the positive electrode active material are 30 wt % and 70 wt %, respectively.

[0191] Examples 24-25

[0192] The difference between Examples 24-25 and Example 1 is that the types of lithium-containing phosphates are different. In Examples 24-25, the lithium-containing phosphates are LiFe 0.5 Mn 0.45 Mg 0.05 PO4、LiMn 0.5 Fe 0.5 PO4.

[0193] Comparative Example 1

[0194] The difference between Comparative Example 1 and Example 1 is that the lithium-rich manganese-based materials are all solid particles.

[0195] Comparative Example 2

[0196] The difference between Comparative Example 2 and Example 1 is that the lithium-rich manganese-based materials are all hollow particles.

[0197] The above-mentioned positive electrode active materials were used to prepare battery cells, and the performance of the battery cells was tested. The specific parameters and test results are shown in Table 1. The preparation and testing methods of the battery cells are described below.

[0198] [Preparation of battery cells]

[0199] (1) Preparation of positive electrode sheet

[0200] The positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 94:4:2. N-methylpyrrolidone was added as a solvent and thoroughly stirred under vacuum to obtain a positive electrode slurry. The positive electrode slurry was then evenly coated on both surfaces of a non-treated positive electrode current collector aluminum foil, ensuring that the coating quality on both surfaces was uniform. The positive electrode sheets were then dried, cold pressed, and slit.

[0201] (2) Preparation of negative electrode sheet

[0202] Artificial graphite, conductive agent acetylene black, binder styrene butadiene rubber (SBR), binder sodium carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95:1.5:3.1:0.4, and deionized water was added as a solvent. The mixture was stirred thoroughly to obtain a negative electrode slurry. The negative electrode slurry was then evenly coated on both surfaces of the negative electrode current collector copper foil without any special treatment, and then dried and cold pressed to a density of 1.65 g / cm 3 , cut to obtain the negative electrode sheet.

[0203] (3) Preparation of electrolyte

[0204] In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), polycarbonate (PC), and dimethyl carbonate (DMC) were mixed in a mass ratio of EC:PC:DMC = 3:3:3. LiPF6 was then added and stirred to obtain an electrolyte solution. The concentration of LiPF6 in the electrolyte solution was 1 mol / L.

[0205] (4) Assembly of battery cells

[0206] The positive electrode sheet, polyethylene (PE) separator, and negative electrode sheet are stacked in order so that the separator is located between the positive electrode sheet and the negative electrode sheet and can isolate the positive electrode sheet from the negative electrode sheet; the stacked components are then wound to obtain an electrode assembly; the electrode assembly is placed in a battery casing, dried, and then injected with electrolyte; after undergoing processes such as formation and standing, a lithium-ion battery cell is obtained.

[0207] [Battery cell performance test]

[0208] (1) Rate performance test

[0209] At 25°C, the lithium-ion battery cell is charged to 4.35V at a constant current rate of 0.1C, then charged at a constant voltage to a current of 0.05C, allowed to stand for 5 minutes, and then discharged to 2.5V at a constant current rate of 0.1C. The discharge capacity at this time is recorded, which is the 0.1C discharge capacity; let it stand for 30 minutes, then the secondary battery is charged to 4.35V at a constant current rate of 0.1C, then charged to a current of 0.05C at a constant voltage, allowed to stand for 5 minutes, and then discharged to 2.5V at a constant current rate of 2C. The discharge capacity at this time is recorded, which is the 2C discharge capacity.

[0210] The rate performance of the battery R = 2C discharge capacity / 0.1C discharge capacity × 100%.

[0211] (2) Volume energy density test

[0212] At 25°C, a lithium-ion battery cell was charged at a constant current of 0.33C to 4.35V, then charged at a constant voltage of 4.35V until the current was less than 0.05C, and then discharged at 0.33C to 2.5V to obtain the discharge energy E. The size of the battery was measured with a vernier caliper, and the volume V was calculated.

[0213] Volume energy density K = E / V.

[0214] As an example, the battery cell model in this embodiment is 406080, and the battery thickness T is approximately 4 mm. This varies with the compaction density of the positive electrode sheet and is subject to actual measurement. The battery cell has a width W = 60 mm and a height H = 80 mm. Based on this, the volumetric energy density is calculated.

[0215] (3) Compaction density measurement

[0216] After the positive electrode is cold pressed (cold pressing pressure is 400KN), the thickness T of the electrode is measured, and the compaction density ρ is calculated based on the thickness T of the positive electrode and the surface density m. 压 The calculation formula is as follows: 压 =m / (TT 箔 ). Where m is the surface density of the electrode g / cm 2 , T 箔 is the thickness of the positive electrode current collector in cm.

[0217] In Table 1, the volume average particle size D of the solid particles is V 50 is represented by D1, the volume average particle size D of the hollow particles V 50 is represented by D2, the volume average particle size D of the hollow particles V 50 and the volume average particle size D of solid particles V The difference of 50 is represented by D3, the size of the cavity of the hollow particle is represented by D4, and the volume average particle size of lithium iron phosphate is D V50 is represented by D5, the mass ratio of lithium-rich manganese-based materials to positive electrode active materials is represented by P, the gram capacity of lithium-rich manganese-based materials is represented by Q, and the compaction density of the positive electrode sheet is represented by ρ 压 The energy density of the battery cell is represented by K, and the rate performance of the battery cell is represented by R.

[0218] Table 1 Specific parameters and test results of the embodiments and comparative examples

[0219] Combining Example 1 with Comparative Example 1, the provision of solid particles and hollow particles in the lithium-rich manganese-based material is beneficial for improving the rate performance of the battery cell; combining Example 1 with Comparative Example 2, the provision of solid particles and hollow particles in the lithium-rich manganese-based material is beneficial for improving the volumetric energy density of the battery cell. Therefore, the technical solutions of the embodiments of the present application are beneficial for balancing the volumetric energy density and rate performance of the battery cell.

[0220] In conjunction with Examples 2-4, by reasonably setting the mass ratio of solid particles to hollow particles, it is beneficial to take into account both the rate performance and energy density of the battery cell. In conjunction with Examples 5-8, 9-12, 13-15 and 18-21, by reasonably setting the particle size of the hollow particles and the particle size of the solid particles, as well as the particle size of the lithium-containing phosphate, it is beneficial to take into account both the rate performance and energy density of the battery cell. In conjunction with Examples 16-17, the selection of suitable lithium-rich manganese-based materials is beneficial to improving the energy density of the battery cell. In conjunction with Examples 22-23, by reasonably setting the mass ratio of lithium-rich manganese-based materials to positive electrode active materials, it is beneficial to take into account both the rate performance and energy density of the battery cell. In conjunction with Examples 24-25, a variety of different materials can be selected as lithium-containing phosphates.

[0221] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and within the scope of the technical solution of the present application, embodiments having substantially the same structure as the technical concept and exerting the same effects are all included in the technical scope of the present application. In addition, within the scope of the subject matter of the present application, various modifications that can be conceived by those skilled in the art to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A positive electrode active material, characterized in that: It comprises a lithium-rich manganese-based material and a lithium-containing phosphate. The lithium-rich manganese-based material comprises solid particles and hollow particles. The hollow particles comprise a shell and a cavity arranged inside the shell.

2. The positive electrode active material according to claim 1, characterized in that In the lithium-rich manganese-based material, the ratio of the mass A of the solid particles to the mass B of the hollow particles is 1:1≤A:B≤9:1; optionally, 7:3≤A:B≤8:2; and / or, In the lithium-rich manganese-based material, the ratio of the number E of the solid particles to the number F of the hollow particles is 70:30≤E:F≤96:4; optionally, 85:15≤E:F≤90:

10.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The volume average particle size D of the solid particles V 50 is 2μm to 8μm; optionally, 3μm to 6μm.

4. The positive electrode active material according to any one of claims 1 to 3, characterized in that The volume average particle size D of the hollow particles V 50 is 5 μm to 15 μm; optionally, is 7 μm to 12 μm.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that The volume average particle size D of the hollow particles V 50 is greater than the volume average particle size D of the solid particles V 50; Optionally, the volume average particle size D of the hollow particles V The difference between the volume average particle size Dv50 of the solid particles and 50 is 3 μm to 10 μm; further optionally, the difference is 4 μm to 8 μm; and / or, The number average particle size of the hollow particles is greater than that of the solid particles; optionally, the difference between the number average particle size of the hollow particles and the number average particle size of the solid particles is 3 μm to 10 μm; further optionally, the difference is 4 μm to 8 μm.

6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The size of the cavity of the hollow particle is 2 μm to 10 μm; optionally, 4 μm to 7 μm.

7. The positive electrode active material according to any one of claims 1 to 6, characterized in that The volume average particle size D of the lithium-containing phosphate V 50 is 0.3μm to 1.5μm; optionally, 0.6μm to 1.2μm.

8. The positive electrode active material according to any one of claims 1 to 7, characterized in that Based on the total mass of the positive electrode active material, the mass proportion of the lithium-rich manganese-based material is P, 10wt%≤P<100wt%; optionally, 30wt%≤P≤70wt%.

9. The positive electrode active material according to any one of claims 1 to 8, characterized in that The gram capacity of the lithium-rich manganese-based material is Q≥153 mAh / g; optionally, Q≥158 mAh / g.

10. The positive electrode active material according to any one of claims 1 to 9, characterized in that The general formula of the lithium-rich manganese-based material is nLi2MnO3·(1-n)Li 1+x1 Ni x2 Mn x3 M 1 x4 O2, where 0.1≤n≤0.3, 0≤x1≤0.1, 0.3≤x2<1, 0<x3≤0.7, 0≤x4≤0.1, M 1 Including one or more of Na, Mg, Al, Ca, Ba, V, Zn, Ti, Fe, Co, Cr, Nb, W, Mo, Zr, Ta, and Hf.

11. The positive electrode active material according to any one of claims 1 to 10, characterized in that The general formula of the lithium-containing phosphate is Li 1+y1 Fe y2 Mn y3 M 2 y4 PO4, where 0≤y1≤0.1, 0≤y2≤1, 0≤y3≤1, 0≤y4≤0.1, M 2 It includes transition metal elements other than Fe and Mn and one or more of non-transition metal elements.

12. A positive electrode sheet, characterized in that: The invention comprises the positive electrode active material as claimed in any one of claims 1 to 11.

13. The positive electrode sheet according to claim 12, characterized in that: The compaction density of the positive electrode sheet is 2.70 g / cm 3 ~2.90g / cm 3 ; Optionally, 2.75 g / cm 3 ~2.85g / cm 3 .

14. A battery cell, characterized in that: The battery cell comprises the positive electrode sheet as claimed in claim 12 or 13.

15. A battery, characterized in that: The battery comprises the battery cell as claimed in claim 14 .

16. An electrical device, characterized in that: The electrical device comprises the battery as claimed in claim 15.

Citation Information

Patent Citations

  • Cathode active material and preparation method thereof, cathode material and lithium ion battery

    CN102569774A

  • Secondary battery

    CN104471749A

  • Positive electrode material for lithium secondary battery and manufacturing method thereof

    CN106450175A

  • Lithium-ion secondary battery

    CN107134562A

  • Nonaqueous electrolyte secondary battery positive electrode active material, method for producing same, and nonaqueous electrolyte secondary battery which uses positive electrode active material

    CN111295786A